„Powstanie więc Polska, co ja mówię? Jest już Polska, a raczej nigdy ona być nie przestała...”. Stracone szanse Konfederacji Generalnej Królestwa Polskiego na odzyskanie suwerenności państwowej - Przygodzki, Jacek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The memorable events that took place in Warsaw from 26th to 28th of June 1812, when the General Confederation of the Kingdom of Poland was established, have long gone into the history of our country. It was then, on the eve of the outbreak of the Second Polish War with the tsarist Russia, that the fate of the creation of an independent Kingdom of Poland was to be determined. It was to be the time when the Polish elites were to pass the exam of maturity in their patriotism and dedication to their homeland. The text analyses the reasons for the lost opportunities for the success of the Polish efforts to create a sovereign state in Poland in 1812.
Keywords: General Confederation of the Kingdom of Poland; Napoléon Bonaparte; Second Polish War; Frederick August I of Saxony; French Invasion of Russia (1812)